Expression of intra-tumoral necrosis-associated cytokine pattern correlated with prognosis and immune status in glioma - Zhao, Hongtao; Dong, Jiawei; Zhang, Jiheng; Wang, Nan; Liu, Zhihui; Yan, Xiuwei; Wang, Fang; Ji, Hang; Hu, Shaoshan (Frontiers in Molecular Neuroscience, 2023)
Intra-tumoral necrosis (ITN) was an independent prognostic factor in glioma. However, the knowledge of ITN was limited to pseudopaliside; the other sides of ITN were relatively neglected. Therefore, a further description of ITN was valuable for understanding its role in glioma. The only reliable ITN model was time-dependently achieved with the GL261 syngeneic mouse model. The ITN-associated expression pattern was enriched from RNA sequencing. TCGA glioma samples were clustered into a high-expression group (HEG) and a low-expression group (LEG) by the verified pattern. Prognosis, clinical status, immune status, and predictive therapeutic responsiveness were compared between the two groups. Invasive histology was observed in mouse glioma with ITN. Cytokine signalling was top enriched in necrotic mouse glioma versus non-necrotic glioma. Nine proinflammatory and two anti-inflammatory cytokine genes were verified to be composed of ITN-associated cytokine patterns. Comparing HEG versus LEG, survival time was nearly half shorter, five clinical statuses were differentially distributed, immune cells were more infiltrated, immune checkpoints were more expressed, and better therapeutic responsiveness was predicted. ITN-associated cytokine pattern is characteristically expressed in glioma with ITN and may imply necrosis missed in histology diagnosis. Expression of the pattern has predictive value in prognosis, tumour grade, immune status, and therapeutic reactivity of glioma.